Levels of Hepatic Activating Transcription Factor 6 and Caspase-3 Are Downregulated in Mice after Excessive Training - Pinto, Ana P.; da Rocha, Alisson L.; Oliveira, Luciana da C.; Morais, Gustavo P.; de Vicente, Larissa G.; Cintra, Dennys E.; Pauli, José R.; Moura, Leandro P.; Ropelle, Eduardo R.; da Silva, Adelino S. R. (Frontiers in Endocrinology, 2017)
Recently, we demonstrated that different running overtraining (OT) protocols with the same external load, but performed downhill (OTR/down), uphill (OTR/up), and without inclination (OTR), led to hepatic fat accumulation. As the disruption of endoplasmic reticulum (ER) homeostasis is linked to animal models of fatty liver disease, we investigated the effects of these OT models on the proteins related to ER stress (i.e., BiP, IRE1, PERK, eIF2alpha, ATF6beta, and GRP94) and apoptosis (CHOP, Caspase-3, 4, and 12, Bax, and TRAF2) in livers of C57BL/6 mice. Also, aerobic training can attenuate cardiac ER stress and improve exercise capacity. Therefore, we investigated whether the decrease in performance induced by our OT protocols is linked to ER stress and apoptosis in mouse hearts. The rodents were divided into six groups: naïve (N, sedentary mice), control (CT, sedentary mice submitted to the performance evaluations), trained (TR), OTR/down, OTR/up, and OTR groups. Rotarod, incremental load, exhaustive, and grip force tests were used to evaluate performance. After the grip force test, the livers and cardiac muscles (i.e., left ventricle) were removed and used for immunoblotting. All of the OT protocols led to similar responses in the performance parameters and displayed significantly lower hepatic ATF6beta values compared to the N group. The OTR/down group exhibited lower liver cleaved caspase-3 values compared to the CT group. However, the other proteins related to ER stress and apoptosis were not modulated. Also, the cardiac proteins related to ER stress and apoptosis were not modulated in the experimental groups. In conclusion, the OT protocols decreased the levels of hepatic ATF6beta, and the OTR/down group decreased the levels of hepatic cleaved caspase-3. Also, the decrease in performance induced by our OT models is not associated with ER stress and apoptosis in mice hearts.